The Second Intron Is Essential for the Transcriptional Control of the Arabidopsis thaliana GLABRA3 Gene in Leaves - Friede, Alexandra; Zhang, Bipei; Herberth, Stefanie; Pesch, Martina; Schrader, Andrea; Hülskamp, Martin (Frontiers in Plant Science, 2017)
The GLABRA3 gene is a major regulator of trichome patterning in Arabidopsis thaliana. The regulatory regions important for the trichome-specific expression of GL3 have not been characterized yet. In this study, we used a combination of marker and rescue constructs to determine the relevant promoter regions. We demonstrate that a 1 kb 5’ region combined with the second intron is sufficient to rescue the trichome mutant phenotype of gl3 egl3 mutants. Swap experiments of the second intron suggest that it is not sufficient to generally enhance the expression level of GL3. This implies that the second intron contains regulatory regions for the temporal and spatial regulation of GL3. The corresponding GUS-marker constructs revealed trichome-specific expression in young trichomes.